2020
DOI: 10.3389/fmolb.2020.00202
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transmembrane 4 L Six Family 1 in the Development and Progression of Cancer

Abstract: Transmembrane 4 L six family 1 (TM4SF1) is a protein with four transmembrane domains that belongs to the transmembrane 4 L six family members (TM4SFs). Structurally, TM4SF1 consists of four transmembrane domains (TM1-4), N-and C-terminal intracellular domains, two extracellular domains, a smaller domain between TM1 and TM2, and a larger domain between TM3 and TM4. Within the cell, TM4SF1 is located at the cell surface where it transmits extracellular signals into the cytoplasm. TM4SF1 interacts with tetraspani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 127 publications
(226 reference statements)
1
51
0
Order By: Relevance
“…With the accumulating evidence for TM4SF1's role in cancer, potential oncologic therapies have been investigated such as in a phase 1/2 clinical trial evaluating chimeric antigen receptor T-cells (CAR-T) to treat patients with TM4SF1-positive pancreatic, colorectal, gastric, and lung cancer (ClinicalTrials NCT04151186). TM4SF1 promotes the migration and invasion of cancer cells by inducing EMT, self-renewal ability, and tumor angiogenesis (26), all of which are mechanisms relevant to the pathological pulmonary vascular remodeling in PAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the accumulating evidence for TM4SF1's role in cancer, potential oncologic therapies have been investigated such as in a phase 1/2 clinical trial evaluating chimeric antigen receptor T-cells (CAR-T) to treat patients with TM4SF1-positive pancreatic, colorectal, gastric, and lung cancer (ClinicalTrials NCT04151186). TM4SF1 promotes the migration and invasion of cancer cells by inducing EMT, self-renewal ability, and tumor angiogenesis (26), all of which are mechanisms relevant to the pathological pulmonary vascular remodeling in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Tm4sf1 was the top upregulated DEG in EA2 vs. EA1 and its expression was specific to EA2 when comparing all lung cell types (Figure E2). Tm4sf1 encodes the cell-surface protein transmembrane 4 L six family member 1 which plays a role in the regulation of cell development, growth and motility and has been strongly implicated in various cancers (26) but has never before been studied in PAH. Given the importance of cancer-related processes and their overlap with PAH (27), we paid closer attention to the Tm4sf1-marked subpopulation of endothelial cells, EA2.…”
Section: Tm4sf1-marked Subpopulation Of Endothelial Cells Expresses a Distinct Transcriptomic Signature Relevant To Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…TM4SF1 is upregulated in several epithelial cancers [ 46 ], including bladder cancer [ 47 ], and promotes the proliferation, migration and invasion of cancer cells by inducing EMT and cancer stemness [ 46 , 48 , 49 ]. Importantly, several studies have shown that TM4SF1 expression is positively correlated with chemotherapy resistance in multiple cancers [ 46 , 50 , 51 ]. IGFBP3 plays a key role in esophageal tumor progression and metastasis by facilitating EMT [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…TM4SF1 has been found to be overexpressed in pancreatic cancer and has roles in apoptosis, proliferation, and cell migration [34]. Previous work found that collagen 1 (GO:0030199) binds with DDR1 which then interacts with TM4SF1 to activate the focal adhesion kinase (FAK) [34,51,52].…”
Section: Spcs Enhances Biological Interpretabilitymentioning
confidence: 99%